2002
DOI: 10.4067/s0717-77122002000100007
|View full text |Cite
|
Sign up to set email alerts
|

Presencia de parásitos intestinales en paseos públicos urbanos en La Plata Argentina

Abstract: With the aim of recovering and identifying parasitic elements we studied soil samples from all public place of La Plata, Argentina (urban area). We surveyed 23 places during March and April, 2000 and at the time of study we measured both the pH and moisture content of each sample taken. We detected 552 parasitic elements, with 98 corresponding to protozoon cysts, 106 to helminth eggs and 348 to nematode larvae. We conclude that the soils in surveyed public places are contaminated with parasites of animal as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
13

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 6 publications
2
12
0
13
Order By: Relevance
“…Likewise, the finding of Toxocara canis and Ancylostoma caninun may produce syndrome of visceral, ocular, neurological, or cutaneous larva migrans in children, as reported by some studies in La Plata (Venturini and Radman, 1988;Minvielle et al, 2003;Córdoba et al, 2002). Furthermore, cestode (tape-worm) eggs from the Taeniidae family could be from Echinococcus spp.…”
Section: Discussionmentioning
confidence: 76%
“…Likewise, the finding of Toxocara canis and Ancylostoma caninun may produce syndrome of visceral, ocular, neurological, or cutaneous larva migrans in children, as reported by some studies in La Plata (Venturini and Radman, 1988;Minvielle et al, 2003;Córdoba et al, 2002). Furthermore, cestode (tape-worm) eggs from the Taeniidae family could be from Echinococcus spp.…”
Section: Discussionmentioning
confidence: 76%
“…52 In recent years, there has been a fairly large amount of research regarding the presence of enteroparasites in domestic dog populations worldwide. 5,7,22,43 Comparatively, fewer studies exist in Argentina 3,12,38,47,56 ; however, only a minority addressed the spatial distribution of infection. 26,46 Several studies reported elevated prevalence of intestinal parasites, mostly among children dwelling in the peripheral and poorest areas of Bahía Blanca, 13,15,17 in vegetables grown in the area (Visciarelli pers.…”
Section: Introductionmentioning
confidence: 97%
“…La contaminación parasitaria del suelo es considerada como un indicador directo de riesgo de infección para los residentes de una región (Córdoba et al, 2002). Se ha estimado que un gramo de materia fecal de un perro cachorro puede contener hasta 15 mil huevos de Toxocara, los cuales, al ser evacuados en la vía pública, son diseminados por el pisoteo, lluvia, viento y vectores.…”
Section: Factores Asociados a La Contaminación Con Toxocara Spunclassified